Neurovascular Shifts, Sensory Sensitivity, and PMDD in Autistic Women: Exploring Blood Flow Redirection, Mood Dysregulation, and Pain Tolerance during Menstruation - Hutson, Piper; Hutson, James (Journal of Community Medicine and Health Solutions, 2024)
This article examines the relationship between Premenstrual Dysphoric Disorder (PMDD), neurovascular dynamics, and sensory sensitivities in autistic women during menstruation. The redirection of blood flow to the uterus during the menstrual cycle has been found to exacerbate cerebral perfusion deficits in neurodivergent individuals, particularly in the Prefrontal Cortex (PFC), which contributes to the mood dysregulation and emotional instability characteristic of PMDD. Autistic women, who often exhibit heightened sensory sensitivities, experience intensified discomfort during menstruation, as sensory overload and altered pain perception compound the emotional challenges of PMDD. These findings emphasize the need for neurodivergent-friendly menstrual products that mitigate both physical and emotional discomfort. Additionally, innovations using biodegradable materials, smart fabrics, and custom-fit menstrual solutions are discussed as potential breakthroughs to improve the quality of life for autistic women managing PMDD. This research highlights the importance of addressing both neurobiological and sensory aspects when designing interventions for PMDD in neurodivergent populations.